Pyrolysis characteristics and kinetics analysis of oil sludge with CaO additive - Chu, Zhiwei (Environmental technology, 2021)
In the process of exploitation, transportation and refining of high-sulfur crude oil, a large number of oil sludge (OS) with high sulfur content is produced. Pyrolysis has been proved to be an effective method for OS disposal, but for solid waste with high sulfur content, lots of sulfur-containing gases will be released during thermal disposal. The addition of calcium oxide in pyrolysis process is an economical and effective way to capture sulfur-containing gases. In order to understand the pyrolysis process of OS with CaO, a thermogravimetric analyser was used to conduct pyrolysis experiments of OS with different Ca/S molar ratios (0, 1, 2 and 3) at different heating rates (10°C/min, 20°C/min, 30°C/min and 40°C/min). The results showed that with the increase of CaO addition the derivative thermogravimetric curves showed a gentle trend. In addition, new weight loss peaks were occurred at 700-900°C and after 1100°C, which were the decomposition of calcium carbonate and calcium sulfate, respectively. The kinetic parameters were solved by Friedman, FWO, and Starink methods, and the results were similar, with an average activation energies (E) value of 214 kJ/mol. The change trend of the activation energy was followed by an increase and then a decrease corresponding to the change of energy demand for the reaction. The calculated average values of ΔH, ΔG and ΔS were about 207, 447 and -0.3250 kJ/mol, respectively. When the conversion rate was 0.5, the thermodynamic parameters reached their maximum values